Thermoelectric device for hypothermia of the human eye - Anatychuk, L.I.; Pasechnikova, N.V.; Kobylianskyi, R.R.; Naumenko, V.O.; Zadorozhnyi, O.S.; Havryliuk, M.V.; Tiumentsev, V.A. (Journal of Thermoelectricity, 2019)
The paper presents the results of the development of a thermoelectric device in the form of a monocular dressing for contact cooling of the human eye through the eyelids. The developed device allows controlled local contact cooling of the eye structures through the eyelids and is designed to treat the acute and chronic eye diseases, reduce intraocular pressure, and reduce pain and inflammatory processes of the eye. The design features of the device and its technical characteristics are presented. Bibl. 23, Fig. 2, table 1.